The role of psychosocial support in enhancing quality of life for cancer patients: challenges and solutions - Jaiswal, Harish; Syed Sabir Ali, Syed Sajid Ali (Journal of Neonatal Surgery, 2025)
Cancer patients encounter many psychological, emotional, and physical obstacles during their diagnosis and treatment. Psychosocial support is essential for improving these people's overall quality of life, even though medical treatments like chemotherapy, radiation, and surgery are necessary for survival. Psychosocial support includes psychological, social, and emotional help for problems like social isolation, anxiety, depression, and coping strategies. In this essay, the significance of psychosocial support in cancer treatment is examined, with particular attention to how it affects both physical and emotional results. It looks at the different kinds of psychosocial interventions that help patients cope with the psychological effects of cancer and its treatments, such as peer mentoring, support groups, counseling, and stress-reduction techniques. Additionally, the paper discusses the obstacles that healthcare systems encounter in delivering sufficient psychosocial care, including a shortage of resources, a shortage of qualified personnel, and the stigma associated with mental health in oncology settings.